A THEME ANALYSIS OF PARATACTIC AND HYPOTACTIC CLAUSE COMPLEXES ON LUKE CHAPTER 17 OF THE ENGLISH STANDARD VERSION BIBLE IN THE ESV.org - Siahaan, Sahat Taruli (Universitas Islam Sumatera Utara (UISU), 2023)
This study aimed to analyze the textual function of the theme types in Luke Chapter 17 of the English Standard Version bible texts on the ESV.org website. The data of this study were English Standard Version (ESV) clauses consisting of 56 clauses from 5 subtopics of Luke Chapter 17, which were analyzed using the qualitative descriptive method because it explains the textual function of biblical texts. The data source for this research is the text of the 2016 edition of the English Standard Version (ESV) Bible on the online Bible site ESV.org. The Gospel of Luke, chapter 17, consists of five subtitles: (1) Temptation to Sin, (2) Increase Our Faith, (3) Unworthy Servants, (4) Jesus Cleanses Ten Lepers, and (5) The Coming of the Kingdom. The theory used in this study is Halliday's Systemic Functional Linguistics. The technical model approach for data analysis in this study is Eggins (2004) regarding (1) four types of themes; (2) theme analysis in declarative sentences; (3) theme analysis in declarative ellipses; (4) theme analysis in the WH interrogative; (5) analysis of themes in imperatives; (6) the theme in the paratactic clause complex; (7) the theme in the hypotactic clause complex; and (8) three types of additions. The results of this study are: 1) four types of themes, namely: (1) topical themes with as many as 46 items (62%), (2) interpersonal themes with as many as 6 items (8%), (3) textual themes. with 19 items (26%) and (4) dual themes with 3 items (4%); 2) topical themes (62%) are the dominant types of themes.